Consumer Sovereignty: Theory and Praxis - Norkus, Zenonas (Problemos, 2003)
The article discusses the principle of consumer sovereignty (considering the satisfaction of consumers' private wants as the ultimate end of economy and most important criterion of economic welfare) which together with the principles of freedom of choice and Pareto optimality constitutes the core of liberal libertarian apology for market economy. As a matter of fact, there are no empirically observable market economies without state regulation of consumption. This regulation includes prohibition to consume some products (e.g., drugs) and services, the restrictions (e.g., alcohol) on and sponsorship for consumption of some other products (e.g., theatre performances). The article discusses whether and under what conditions state regulation of consumption is paternalist and when it is consistent with consumer sovereignty. The consumer welfare (defined by the satisfaction of private (self-regarding) wants) is considered as only a special aspect of total social welfare (including also the satisfaction of non-partial other-regarding (ethical) wants) which is theoretically inconsistent concept because of the unsolved aggregation problems disclosed by famous Arrow theorem. Because of the pluralism of ethical values, visions of good life and good society characteristic for (post)modern Western society, consumer sovereignty is considered as the only viable foundation of economic politics committed to values of tolerance and negative liberty.
Keywords: consumer sovereignty; freedom of choice; Pareto optimality; consumer and social welfare; state regulation of consumption.